Students’ Perceptions of Quizizz as a Formative Assessment Tool for Reading Comprehension in EFL Learning - Dea Alawiah Amini; Wahyu Satya Gumelar; Riki Ruswandi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The primary purpose of this study was to explore the application of Quizizz as a formative assessment tool in teaching reading comprehension in English as a Foreign Language (EFL) classrooms. This study examines high school students’ perceptions of quizzes as a formative assessment tool for reading comprehension within EFL contexts. It focuses on increasing digital-based learning engagement among high school students. Using a quantitative research design, this study surveyed 58 eleventh-grade students from SMA PGRI 2 Bandung who had experience using Quizizz in reading activities. Data were collected through a validated 27-item questionnaire using a 5-point Likert scale (Cronbach's Alpha = 0.898). The results revealed that the average student response was in the "High" category (M = 3.43), indicating positive perceptions across aspects such as interactivity, gamification, feedback effectiveness, and ease of use. However, some students reported challenges, including time pressure and technical limitations. This study suggests quizzes can be an effective tool for formative assessment of reading comprehension, especially when integrated with supporting instruction. The broader implications emphasize the importance of digital literacy among teachers and the need for infrastructure to support gamified assessment in EFL learning.